2016
DOI: 10.1071/cp15214
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of high intensity crop rotation and N management on oilseed rape productivity in Germany

Abstract: A rotational field experiment was established in the year 2002 at the experimental farm Etzdorf in the Hercynian dry region of central Germany. Since 2005 field measured datasets were used to determine the effect of different preceding crop combinations and different nitrogen (N) fertilisation treatments on the seed yield, oil content, oil yield and N-use efficiency of oilseed rape (Brassica napus L.). The preceding crop combinations compared were winter wheat (Triticum aestivum L.)-winter wheat (WW), WW-oilse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Recent studies have revealed considerable scope for improvement in NUE of oilseed rape ( Weiser et al , 2017 ). This can be partially achieved by approaches that simultaneously consider crop management ( Hegewald et al , 2016 , 2017 ; Kirkegaard et al , 2016 ), more accurate prediction of N requirement ( Barlog and Grzebisz, 2004 a , b ; Henke et al , 2007 ), timing of N fertilization ( Berry and Spink, 2009 ; Gombert et al , 2010 ), and more contemporary, precise application of N fertilizer. On the other hand, appropriate use of genetic variation to increase yield has been recognized as a major driver of sustainable production.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed considerable scope for improvement in NUE of oilseed rape ( Weiser et al , 2017 ). This can be partially achieved by approaches that simultaneously consider crop management ( Hegewald et al , 2016 , 2017 ; Kirkegaard et al , 2016 ), more accurate prediction of N requirement ( Barlog and Grzebisz, 2004 a , b ; Henke et al , 2007 ), timing of N fertilization ( Berry and Spink, 2009 ; Gombert et al , 2010 ), and more contemporary, precise application of N fertilizer. On the other hand, appropriate use of genetic variation to increase yield has been recognized as a major driver of sustainable production.…”
Section: Introductionmentioning
confidence: 99%
“…Oilseed rape ( Brassica napus L.) is a major oil crop in Europe, and the harvested area doubled from 2001 to 2018 (FAOSTAT, 2020) following the rise in biodiesel production (Hamelinek, De Loveinfosse, & Koper, 2014). The cultivation of oilseed rape demands high amounts of nitrogen (N) fertilizer, to gain sufficient yield (Hegewald, Koblenz, Wensch‐Dorendorf, & Christen, 2016). The harvest index of oilseed rape is low, which results in high N surpluses post‐harvest (Sieling & Kage, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the intensity of canola production and its frequency in the crop sequence generates a significantly increased risk of Blackleg, which requires increased attention to in-paddock stubble management, separation from nearby infected residues and the rotation of canola varieties according to major resistance genes (Van de Wouw et al 2016). In Germany, where canola area doubled to 1.5 Mt from 1990 to 2013 at a time when total agricultural area declined, Hegewald et al (2016) have demonstrated associated reduction in seed yield (12%) and oil yield (14.6%) associated with increasing the intensity of canola production, despite full fungicide programs applied to the crops. Although the cause of the yield decline in that study was not identified, similar studies in Canada using spring canola have demonstrated increased Blackleg incidence and root-maggot (Della spp.)…”
Section: Farming Systems Evolution and Tactical Agronomymentioning
confidence: 99%
“…In this Special Issue of Crop & Pasture Science we present an up-to-date summary of the recent and future trends in genetics, plant breeding, crop physiology and modelling, pathology, and farming systems agronomy in Australian canola production systems, at a time when the area and production are at an all-time high. We also present recent reviews of production trends in other established canola-producing nations including Canada (Morrison et al 2016a) and Germany (Hegewald et al 2016) along with the challenges of the fledgling industry in the Pacific North-west of USA (Pan et al 2016) where farmers and scientists face many of the same biophysical, socioeconomic and marketing challenges that faced the pioneering Australian farmers and technologists in the 1970s and 1980s. In this paper we introduce some of the key changes and drivers of recent trends in canola productivity in Australia, highlight aspects of some of the research presented herein, and discuss the impact of these results on future Australian canola production.…”
Section: Introductionmentioning
confidence: 99%